PENGERTIAN, TEORI DAN KONSEP, RUANG LINGKUP ISU-ISU KONTEMPORER PENDIDIKAN ISLAM - Destrianjasari, Sherin; Khodijah, Nyayu; Suryana, Ermis (Jurnal Ilmiah Mandala Education (JIME), 2022)
Learning starts from the understanding that Islamic education has a very important role in shaping the true Muslim personality. Generations of young Muslims must be educated based on the concept of Islamic education so that they can contribute positively to meeting the needs of the people and the general public. This learning study is very important in providing direction on issues of Islamic education reform such as learning methods, curriculum development and teaching approaches that are directly related to the effectiveness of Islamic education in Islamic educational institutions.The questions that arise are what is the meaning of contemporary issues, what are the theories and concepts of contemporary issues, and what is the scope of contemporary issues. In addition, this paper also explains the issues that occur and the renewal that gives rise to new thoughts along with the structural and cultural changes of the times in the field of education in an Islamic education institution.